2008
DOI: 10.1016/j.ccr.2007.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Plexiform and Dermal Neurofibromas and Pigmentation Are Caused by Nf1 Loss in Desert Hedgehog-Expressing Cells

Abstract: Neurofibromatosis type 1 (Nf1) mutation predisposes to benign peripheral nerve (glial) tumors called neurofibromas. The point(s) in development when Nf1 loss promotes neurofibroma formation are unknown. We show that inactivation of Nf1 in the glial lineage in vitro at embryonic day 12.5 + 1, but not earlier (neural crest) or later (mature Schwann cell), results in colony-forming cells capable of multilineage differentiation. In vivo, inactivation of Nf1 using a DhhCre driver beginning at E12.5 elicits plexifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
3
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(252 citation statements)
references
References 50 publications
13
223
3
2
Order By: Relevance
“…A follow-up study using reciprocal bone-marrow transplantation between Nf1 +/-and Nf1 +/+ mice provide evidence that an Nf1 +/-c-Kit expressing hematopoietic cell contributes strongly to the plexiform neurofibroma phenotype, independent of Cre-mediated recombination ). In contrast, recent studies have reported the generation of plexiform neurofibromas in a wildtype Nf1 environment (Wu et al 2008) and that wildtype mast cells can contribute to tumor formation (Monk et al 2007). With the data presented in this paper, we can now reconcile these seemingly disparate results, clarifying the role of the Nf1 +/-microenvironment in peripheral nerve sheath tumorigenesis.…”
Section: The Contribution Of the Nf1 Heterozygous Environmentsupporting
confidence: 50%
“…A follow-up study using reciprocal bone-marrow transplantation between Nf1 +/-and Nf1 +/+ mice provide evidence that an Nf1 +/-c-Kit expressing hematopoietic cell contributes strongly to the plexiform neurofibroma phenotype, independent of Cre-mediated recombination ). In contrast, recent studies have reported the generation of plexiform neurofibromas in a wildtype Nf1 environment (Wu et al 2008) and that wildtype mast cells can contribute to tumor formation (Monk et al 2007). With the data presented in this paper, we can now reconcile these seemingly disparate results, clarifying the role of the Nf1 +/-microenvironment in peripheral nerve sheath tumorigenesis.…”
Section: The Contribution Of the Nf1 Heterozygous Environmentsupporting
confidence: 50%
“…The bi-allelic inactivation leading to the development of plexiform neurofibromas apparently takes place in embryonic cells that have the potential to generate large populations of cells carrying a single NF1 second-hit mutation. 77,81 The growth of plexiform neurofibromas during early childhood distinguishes these tumors from cutaneous neurofibromas, which are undetectable before puberty. 5 Mouse studies have demonstrated that Nf1 Ϫ/Ϫ Schwann cells are necessary, but not sufficient, for tumor formation to occur.…”
Section: Pathogenesis Of Plexiform Neurofibromasmentioning
confidence: 99%
“…While data from certain mouse models suggest that tumor formation requires Nf1 +/− mast cells, other models using developmentally earlier and more widespread glial cell deletions have not shown this requirement for Nf1 +/− mast cells [46]. Regardless, all mouse models to date have shown the pervasive presence of degranulating mast cells within the tumor tissue.…”
mentioning
confidence: 99%